2001
DOI: 10.1088/0741-3335/43/11/305
|View full text |Cite
|
Sign up to set email alerts
|

A non-local synergism between electron cyclotron waves and lower hybrid waves induced by transport

Abstract: In this paper, we study the effects of particle radial transport on the electron cyclotron (EC) and lower hybrid (LH) power deposition profiles and current drive efficiency. We consider a tokamak plasma under the combined action of LH waves, EC waves, collisions and spatial transport of electrons across the magnetic surfaces, and consider situations in which the spatial location of the peaks of power deposition profiles for EC and LH waves is not the same. Our results, found from numerical solution of the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…We have obtained curves very similar to those of figure 2, which also are not be shown for the sake of brevity. Nevertheless, we mention that it is possible to note from the results that the particle accumulation at the barrier region is more pronounced than in the case shown in figure 2, for increasing EC power level, because the transport is more significant for high-energy particles, whose population increases with the increase of P ec (Rosa and Ziebell 2001).…”
Section: Numerical Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…We have obtained curves very similar to those of figure 2, which also are not be shown for the sake of brevity. Nevertheless, we mention that it is possible to note from the results that the particle accumulation at the barrier region is more pronounced than in the case shown in figure 2, for increasing EC power level, because the transport is more significant for high-energy particles, whose population increases with the increase of P ec (Rosa and Ziebell 2001).…”
Section: Numerical Resultsmentioning
confidence: 67%
“…It has also been shown that the EC absorption is very sensitive to the local particle density. When transport is present in the plasma, a consequence is the change in the density profile and therefore in the cyclotron absorption (Rosa and Ziebell 2001). If different kinds of transport are present, in particular in the presence of ITBs, it is therefore interesting to investigate the consequences for the EC absorption and the ensuing modifications in the EC + LH efficiency.…”
Section: Introductionmentioning
confidence: 99%